TEKNIK PENERJEMAHAN TINDAK TUTUR DIREKTIF DALAM CERPEN DOKTOR SIHIR KARYA IWAYA SAZANAMI DAN LARILAH MELOS KARYA DAZAI OSAMU - Reny Wiyatasari (IZUMI, 2015)
This paper aims to identify the technique translation of directive speech act that used in two Japanese stories of Mahou Hakushi by Iwaya Sazanami and Hashire Merosu by Dazai Osamu. Those stories are two translation works of Japanese literature in the book of Antologi Kesusastraan Anak Jepang (Nihon Jidou bungaku Senshuu). This book contains children’s literature that translated from Japanese to Indonesian by Antonius Pujo. Those two stories selected because there are many speech act in that, and the directive is considered as most interesting speech act than the other ones. This paper used descriptive qualitative method. The total number of the collected  data are 50. The result show there are seven types of translation technique with total usage frequency 72 times. Those techniques are as follow : amplification 18 times, linguistic amplification 16 times, estabilsh equivalent 15 times, literal translation 11 times, reduction 5 times, modulation 5 times, transposition 2 times.